Mindfulness: Embrace Mental Well-Being with A Healthy Perception of Stress - Hutapea, Imelda Lan Maretny; Lubis, Rahmi; Patisina, Patisina; Choong, Thum Chern (TAZKIYA Journal of Psychology, 2025)
Prioritising mental well-being in the workplace helps promote a productive and healthy working environment. Stress is one of the main determinants of mental well-being in employees. Stress caused by daily challenges at work will impact mental well-being. In modern times, there is an increasing acceptance of stressful conditions and mental health issues. Mindfulness is one of the ways to improve mental well-being and buffer stress in employees. This study examines the effect of mindfulness on mental well-being by considering the mediating role of perceived stress in employees working on a shift system. This study is motivated by the high risk of mental health disorders in shift workers due to irregular work patterns, high workload, and lack of recovery time. This study used three psychological instruments: the mindfulness scale (FFMQ), the perceived stress scale (PSS), and the mental well-being scale (WEMWBS), including 540 respondents from company X in Medan City, and using the SEM-PLS 4.0 method. The results showed that mindfulness significantly improved mental well-being (β=.388, p<.005) and reduced perceived stress (β=-.493, p<.005), whereas perceived stress was shown to decrease mental well-being (β=-.174, p<.05). The crucial finding showed that perceived stress was a partial mediator (β=.086, p<.05). Theoretically, this study enriches the literature by confirming the mediating mechanism of perceived stress within the framework of mindfulness and mental well-being, particularly in the underrepresented population of shift workers in previous studies. In practical terms, the results suggest three programme modifications that companies can implement: (1) a corporate well-being programme that includes mental health interventions specifically for shift workers, (2) a mobile application with brief interventions for stress management during shifts, and (3) a shift rotation system tailored to workers' natural productive time tendencies (chronotype).